2017
DOI: 10.5688/ajpe81233
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Holistic Assessment Plan to Evaluate a Four-Semester Laboratory Course Series

Abstract: Objective. To implement a holistic assessment plan to evaluate the impact of a four-semester laboratory course series entitled Integrated Pharmacotherapy Skills on students' readiness to begin advanced pharmacy practice experiences (APPEs) following separation of the laboratory component from the Pharmacotherapy lecture component. Design. Faculty prospectively selected and employed a variety of course assessment methods including student self-and preceptor evaluation during APPEs, course evaluations, and a stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…There is value in considering both students' and instructors' perceptions of assessments, as they can differ, and our next steps should triangulate student feedback as well as their confidence related to practice readiness with that of faculty perspectives. 8,10,[24][25][26] Third, although no student failed more than two assessments in this cohort, the possibility remains that this may be the case in future cohorts which is why continuous monitoring of student performance in each assessment, and careful blueprinting of assessments (adequately plan how assessments align and overlap with intended objectives) is required to ensure effective learning towards practice readiness. Finally, as we only considered one course, mapping all assessments across the program may provide further evidence of student practice readiness.…”
Section: Discussionmentioning
confidence: 97%
“…There is value in considering both students' and instructors' perceptions of assessments, as they can differ, and our next steps should triangulate student feedback as well as their confidence related to practice readiness with that of faculty perspectives. 8,10,[24][25][26] Third, although no student failed more than two assessments in this cohort, the possibility remains that this may be the case in future cohorts which is why continuous monitoring of student performance in each assessment, and careful blueprinting of assessments (adequately plan how assessments align and overlap with intended objectives) is required to ensure effective learning towards practice readiness. Finally, as we only considered one course, mapping all assessments across the program may provide further evidence of student practice readiness.…”
Section: Discussionmentioning
confidence: 97%
“…Process and product assessment are to provide a comprehensive picture of students' abilities. These two components will provide teachers with information about the ability to work in the classroom of students (Porter et al, 2017). Student performance assessment is an alternative for teachers to assess students' abilities for cognitive and psychomotor aspects of students (Chen et al, 2013;Cougar Hall & West, 2011).…”
Section: Rating Scale Functionalitymentioning
confidence: 99%
“…This model provides explicit examples of how to create rapport, elicit patient concerns and ideas, explore the illness experience, and convey empathy and can be helpful to other health care professionals wishing to improve their communication skills. The Four Habits Model was used as a foundation for the development of the Patient-Centered Communication Tools (PaCT) to measure pharmacy students’ communication skills [ 42 ].…”
Section: Pharmacists and Patient-centered Communicationmentioning
confidence: 99%
“…When comparing the PaCT and the Four Habits Model on the same performance, scores were significantly correlated. According to the authors, the instrument demonstrated significant face, content, construct, and test–retest validity [ 42 ].…”
Section: Pharmacists and Patient-centered Communicationmentioning
confidence: 99%